KEPEMIMPINAN MUSIKAL SEBAGAI KATALISATOR KETERLIBATAN JEMAAT DALAM IBADAH - Zelfianus, Rudy (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2025)
ABSTRACT This research explores the critical role of music leadership in fostering congregational engagement during Christian worship. Focusing on the Imanuel GPM Amahusu congregation in Ambon, this study investigates how music leaders act as catalysts for emotional and spiritual connection through the harmonious integration of theological principles, local cultural elements, and modern musical aesthetics. Using a qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis. Thematic analysis revealed three main themes: the collaborative role of music leaders, adaptation to modern music preferences, and preservation of traditional liturgical values. To ensure data validity, triangulation, discussion with experts, and member checking methods were used. The findings highlight the strategic contribution of music leadership in balancing innovation and tradition, creating transformative worship experiences. The research contributes a new framework for understanding the role of music leadership in enhancing congregational engagement and offers practical insights for church leaders in navigating the complexities of modern worship contexts. It underscores the need for ongoing training and collaboration among music leaders to maintain the relevance and spiritual impact of liturgical practices in a pluralistic society. Keywords: Keywords: music leadership, congregational engagement, Christian worship.